THE ROLE OF SUSTAINABLE MARKETING IN CREATING VALUE FOR CUSTOMERS AND SOCIETY - Moh. Yamin Darsyah; Felina C Young; Mohammad Taqiuddin Mohamad; Mohd Syahrin; Al-Amin (Adisam Publisher, 2024)
In the past decade, global awareness regarding sustainability has increased, fueling greater demand for socially and environmentally responsible business practices. This has led to the development of sustainable marketing as a key strategy for companies to not only meet consumer expectations but also to act as leaders in sustainability. This study aims to explore the effectiveness of sustainable marketing in creating value for consumers and companies. The study conducted in this research uses the literature research method. The results show that authenticity, transparent communication, and meaningful interaction with consumers are key factors in the effectiveness of sustainable marketing. Long- term success is also closely related to the company's ability to effectively integrate sustainability efforts into all aspects of business operations, from procurement to point of sale. The findings emphasize the importance of a holistic approach to sustainability marketing to create substantial value for consumers, increase brand loyalty, and positively influence firm performance.